An Investigation on Learning Performance among Disabled People Using Educational Multimedia Software: A Case Study for Deaf People - Masitry, Ananthi Krishnasami; Majid, Mazlina Abdul; Toh, M Zulfahmi; Herawan, Tutut (2013)
The increasing number of people with hearing-impaired in Malaysia attracts to produce a variety of technologies, which can assist the deaf people in carrying out their tasks in everyday life as normal people. New technology can help to decrease the difficulty that hearing-impaired people faces in daily life to use the information services like normal people. Thus, this paper focuses on: i) developing a new multimedia courseware for pre-school students with hearing problem, and ii) comparing the deaf student’s learning performance before and after using the courseware. Four modules were developed for e-MSL courseware consist of alphabets, numbers, words and quizzes with colorful text, animation, sounds, video and pictures using Malaysian Sign Language (MSL). Sekolah Rendah Pendidikan Khas (SRPK) Indera Mahkota II, Kuantan has been chosen as the case study for data collection and for investigating the student learning performance on the courseware. The survey results show that 100% of the respondents have agreed that using e-MSL courseware managed to reduce the student learning time more than 80%. The result has indicated that students have shown better learning performance using e-MSL compared to traditional learning.
KerkoCite.ItemAlsoKnownAs: 10.14257/ijbsbt.2013.5.6.02 2339240:6YFB5WG4 2405685:XDQ6E2DZ

An investigation on learning Performance among disabled people using educational multimedia software: A case study for deaf people - Masitry, Ananthi Krishnasami; Majid, Mazlina Abdul; Toh, M. Zulfahmi; Sutarman, Sutarman; Herawan, Tutut (International Journal of Bio-Science and Bio-Technology, 2013)
The increasing number of people with hearing-impaired in Malaysia attracts to produce a variety of technologies, which can assist the deaf people in carrying out their tasks in everyday life as normal people. New technology can help to decrease the difficulty that hearing-impaired people faces in daily life to use the information services like normal people. Thus, this paper focuses on: i) developing a new multimedia courseware for pre-school students with hearing problem, and ii) comparing the deaf student’s learning performance before and after using the courseware. Four modules were developed for e-MSL courseware consist of alphabets, numbers, words and quizzes with colorful text, animation, sounds, video and pictures using Malaysian Sign Language (MSL). Sekolah Rendah Pendidikan Khas (SRPK) Indera Mahkota II, Kuantan has been chosen as the case study for data collection and for investigating the student learning performance on the courseware. The survey results show that 100% of the respondents have agreed that using e-MSL courseware managed to reduce the student learning time more than 80%. The result has indicated that students have shown better learning performance using e-MSL compared to traditional learning.
12 citations (Crossref) [2024-02-28] KerkoCite.ItemAlsoKnownAs: 10.14257/ijbsbt.2013.5.6.02 2339240:FFTDSD2U 2405685:LMG42B3J
Keywords: ⛔ No INSPIRE recid found

E-learning tools for public awareness programme education in disaster risk management: Case study of the city of Cape Town disaster risk management centre - Kabaka, Martha; Stoltenkamp, Juliet (Proceedings of the International Conference on e-Learning, ICEL, 2013)
Disaster occurrence around the world has in the past few decades increased at an alarming rate necessitating an urgent need for mitigation strategies. As a result, research has indicated the usefulness of Information Communication Technology (ICT) in disaster risk management. Furthermore, ICT generally plays a critical role in all aspects of disaster risk management such as: early warning prediction; informing and circulating information relating to disasters to communities especially those at risk as promptly as possible and providing communication structures immediately after a disaster occurrence. As part of its planning and precautionary measures in responding to disasters, the City of Cape Town Disaster Risk Management Centre (CoCTDRMC) implements public awareness programmes across the city. The most acclaimed is an annual awareness programme especially for high school learners selected from various schools across the city. The learner participants are expected to act as change agents in their communities. In 2012, learners from twelve different schools across the city benefited from this programme. They were expected to educate families, friends, schoolmates and communities generally on the topical issues surrounding disaster risk management. This study uses a case study approach. Since the target audience of the programme is the youth, there is need to shift towards utilising ICT. The aim of this paper is to look at how e-learning as an ICT tool can be integrated in the implementation of Public Awareness Education Programme (PAEP), so as to target broader audience and create an increased capacity building across the City of Cape Town (CoCT). The examination considers providing tools that are accessible, dependable, resilient and flexible among the residents so as to reach the grassroots levels where communities are mostly affected. The paper considers a combination of tools so as to support behavioural change. Some of the research findings are that, the 2012 programme was very beneficial and successful. Henceforth there is need to target a broader audience, and although the CoCTDRMC does make use of some relevant ICTs, there is need for additional and upgraded technological resources. Also pertinent is the fact that e-learning can play a major role in making sure that a broader audience is reached if applied effectively. The findings of the research are of relevance to the CoCTDRMC and other municipalities across South Africa. The Centre for Innovative Educational and Communication Technologies (CIECT) at the University of the Western Cape can also use these findings to develop and implement an e-learning course for both employees of CoCTDRMC and other interested community members. This will guide them on how e-learning can assist in fostering a successful implementation of PAEP across the city.
KerkoCite.ItemAlsoKnownAs: 2405685:JM85NT5X
Keywords: Disaster; Disaster risk management; E-learning; Information communication technology; Public awareness education programme; ⛔ No DOI found

Towards the development of mobile learning model for Tanzania secondary schools: Case study Kilimanjaro region - Chambo, F. F.; Laizer, L. S.; Nkansah-Gyekye, Y.; Ndume, V. (2013 Pan African International Conference on Information Science, Computing and Telecommunications (PACT), 2013)
This paper explores the factors that influence the implementation of m-learning and proposes a model for implementing m-learning in Tanzania. The study was conducted in ten secondary schools in the Kilimanjaro region in Tanzania. Purposive and convenience sampling techniques were used to determine students majoring in science subjects. Findings indicate that majority of students own mobile phones and have access to the Internet connectivity. However, m-learning platforms that are currently in place are not viable solution in all contexts and not necessarily the best solution. Therefore, the design of m-learning content should focus on learning profile and personal needs such as location and affordability. A framework that considers four factors: user satisfaction, pedagogy, technology, and economy of use are proposed for Tanzanian context. It is concluded that education stakeholders should consider the opportunities of technology in education in order to boost knowledge sharing among students.
KerkoCite.ItemAlsoKnownAs: 10.1109/SCAT.2013.7055102 2339240:STRH6VLC 2405685:BPEQ8EVG
Keywords: Computational modeling; Context modeling; Educational institutions; Internet; Internet connectivity; Interoperability; Kilimanjaro region; Learning Science; M-Learning; Materials; Mobile handsets; Secondary School; Tanzania secondary school; computer aided instruction; economy of use; education stakeholder; emerging technology; knowledge sharing; m-learning; mobile learning; mobile learning model; mobile phone; pedagogy; sampling methods; sampling technique; science subject; user satisfaction

Digital Study Hall: Lighthouse Case Study - Dover, Mark (Global Solution Networks, 2013)
EdTechHub.ItemAlsoKnownAs:2405685:MA8GBA4K

Digital literacy in Ugandan teacher education: Insights from a case study - Andema, Samuel; Kendrick, Maureen; Norton, Bonny (Reading & Writing-Journal of the Reading Association of South Africa, 2013)
Publisher: AOSIS KerkoCite.ItemAlsoKnownAs: 2405685:EMRHZ4XF
Keywords: ⛔ No DOI found

Implementation of Information and Communication Technologies (ICTs) in Education Course: A Case from Teacher Education Institutions in Pakistan - Majoka, Muhammad Iqbal; Fazal, Shawana; Khan, Muhammad Saeed (Bulletin of Education and Research, 2013)
This research was aimed to explore the implementation of Information and Communication Technologies (ICTs) in education in teacher training programs in the Khyber Pakthunkhwa and Punjab provinces in Pakistan. It was the first time that the course "ICTs in Education" was implemented for ADE/B. Ed (Elementary) programs in session 2010-11. In this situation, it was vital to explore how successfully this course was implemented in the pioneer institutions, so as to have baseline information for further improvement in the implementation process. This study was focused to explore: (i) How the course "ICTs in Education" was implemented? (ii) How did the teacher educators follow the course guide and to what extent the course guide was helpful in implementing this course? Seven teacher training institutions (three from the Punjab and four from KP provinces) were selected as target population. The total sample was 40 teacher educators and 200 students from seven institutions. Mixed method research design was adopted to conduct this study. The data was drawn from the surveys for heads and prospective teachers, and semi-structured interviews with teacher educators. Analysis revealed that only in a few classrooms, different activities/ experiences as suggested in the unit were properly implemented, while in most that was not the case due to issues such as shortage of electric power supply, scarcity of ICTs tools and lack of training and skills in ICTs application. The extent to which teachers followed the course guide was another factor contributing to the implementation process.
Publisher: Institute of Education and Research KerkoCite.ItemAlsoKnownAs: 2339240:ZE68BKG6 2405685:SEX5IS4Z
Keywords: Barriers; Energy; Foreign Countries; Guides; Information Technology; Program Implementation; Teacher Education Programs; Teacher Educators; ⛔ No DOI found

Reciprocity among Farmers in Farming System Research: Application of Social Network Analysis - Jana, Rabindranath; Bandyopadhyay, Suraj; Choudhuri, Anil K. (Journal of Human Ecology, 2013)
In course of agricultural activities, farmers interact among themselves to fulfill different kinds of needs, such as getting advice regarding cultivation, obtaining appropriate seeds and plants, getting tools and implements, etc. On the basis of data to whom a farmer sends requests for such help and whether the farmer receives the required help, one can build a social network of help, whether simple or weighted, in agricultural production. The paper intends to study variation in measures of reciprocity among the farmers of the two villages in respect of different activities for agricultural production. For the study, two villages Madhya-Uttar and Astabari consisting of 88 and 79 households respectively were selected from unirrigated, rainfed area in the south-eastern region of the district of East Medinipur of West Bengal. To collect the required data, open-ended check lists were employed. A standardized graph theoretic measure (s3-measure) of reciprocity was applied to carry out social network analysis. In both the villages, values of reciprocity measures for seeds/plants and tools/implements exchange were more than that for advice giving; the measure for the network of agricultural activities as a whole was also greater than the network for social aspects. In case of all networks, values of s3-measure for the village Madhya-Uttar were much higher than Astabari. It indicates that the farming households of a network having greater value of s3-measure are more inter-dependent among themselves in agricultural production.
Publisher: Routledge _eprint: https://doi.org/10.1080/09709274.2013.11906552 zotzenLib.CopiedFrom: 2339240:FI73YH85 KerkoCite.ItemAlsoKnownAs: 10.1080/09709274.2013.11906552 2339240:FI73YH85 2405685:8VW4AE3P
Keywords: In-degree; Out-degree; Reciprocal Pair; Simple and Weighted Social Networks; s3-measure

Designing OLPC learning environments: A case on 1:1 pedagogy in rural Tanzania - Pakarinen, S.; Apiola, M.; Moisseinen, N.; Tedre, M. (2013 Africon, 2013)
In the past two decades computers have become a standard educational tool in the industrialized countries. Recently, equipping each student with a personal device (one-to-one computing, OLPC) has been enthusiastically advocated for developing countries, too. However, despite a number of pioneering research studies, broader analyses of pedagogical, technical, and organizational aspects of one-to-one computing in developing countries are largely missing. In this participatory action research in a rural Tanzanian primary school, we identified a number of pedagogical elements that were beneficial for teaching and utilizing ICT in the classroom. We pinpointed exploratory and self-regulated learning, group problem solving, and constructive principles as facilitators of learning within the one-to-one computing paradigm in this context. Our results show that the introduction of children's computers also triggered a number of changes in dynamics both within the school but also outside the school.
ISSN: 2153-0033 KerkoCite.ItemAlsoKnownAs: 10.1109/AFRCON.2013.6757660 2339240:W653CXZ9 2405685:8SFQ3SZ7
Keywords: Context; Educational institutions; ICT utilization; Interviews; Materials; OLPC learning environment; Portable computers; Tanzania; computer aided instruction; constructive principles; educational institutions; educational tool; exploratory learning; group problem solving; information and communications technology; learning facilitators; one-to-one computing; organizational aspect; participatory action research; pedagogical aspect; pedagogical elements; pedagogy; rural primary school; self-regulated learning; teaching; technical aspect

Negotiating problems of practice in research–practice design partnerships - Penuel, William R.; Coburn, Cynthia E.; Gallagher, Daniel J. (Teachers College Record, 2013)
This chapter focuses on how researchers and practitioners negotiate the focus of their joint work within design-based implementation research (DBIR). Studying and facilitating successful negotiation of the problems that become the focus of work and the search for solutions is important for developing DBIR, because of its commitment to focusing on persistent problems of practice from multiple stakeholders’ perspectives. Case studies of two different research–practice partnerships provide a context for exploring two different perspectives on negotiation. In one case study, the notion of partnerships as forms of cultural exchange across institutional boundaries that differ with respect to goals, norms, and practices is used to analyze a design partnership focused on repurposing curriculum units in elementary science. In the second case study, the concept of framing as developed in social movement theory is used to illuminate issues of status and authority within a partnership between a district and researchers. The chapter concludes by describing the contributions of each perspective to an understanding of how teams jointly negotiate the focus of their work and by providing some recommendations for how teams can do so successfully.
Publisher: SAGE Publications KerkoCite.ItemAlsoKnownAs: 10.1177/016146811311501404 2339240:SYWMCASG 2405685:TPCFE4PT

Motivating students to offer their best: evidence based effective course design - Stearns, Susan A. (College Teaching, 2013)
Sometimes we question whether students are incapable or capable and/or willing or unwilling in regards to their academics. This study determined where students lie in regards to these concepts and showed one example of motivating students to do their best via course design, in this particular case by the use of a writing process model.
Publisher: Routledge _eprint: https://doi.org/10.1080/87567555.2013.809328 KerkoCite.ItemAlsoKnownAs: 10.1080/87567555.2013.809328 2339240:EF69M7DI 2405685:ZQ7IH9JT
Keywords: course design; effective teaching; higher education; process writing; student motivation

Teachers’ Perception About Integration of ICT in Teaching and Learning of Kiswahili Language in Secondary Schools in Kenya. - Miima, Florence; Ondigi, Dr Samson; Mavisi, Rose (2013)
This article discusses the results of exploratory study of integration of ICT in teaching and learning of Kiswahili language in Kenyan secondary schools taking the case of Kakamega county in western part of Kenya. A survey design technique was adopted. Forty five teachers were selected to act as sample size for the study. Questionnaires and interview protocols were used to collect the data. The data collected was analyzed through descriptive statistical techniques. The results are summarized and presented through tables and graphs. The findings established that most Kiswahili teachers understand the benefit of integrating ICT in teaching and learning of Kiswahili language but they are not willing to adopt it due to various challenges. The paper examines how Kiswahili language teachers integrate ICT into everyday classroom practice, their perceptions, constrains, and their reservations. It also considers use of ICT along with the influences of established curriculum practice and policy upon Kiswahili language teacher’s willingness to develop new forms of activity and pedagogy. The case study provides some information on integration of ICT at all level of language teaching and learning in education.
KerkoCite.ItemAlsoKnownAs: 2339240:877NW8X7 2405685:7X9VB3JM

Computer literacy and e-learning perception in Cameroon: the case of Yaounde Faculty of Medicine and Biomedical Sciences - Bediang, Georges; Stoll, Beat; Geissbuhler, Antoine; Klohn, Axel M; Stuckelberger, Astrid; Nko’o, Samuel; Chastonay, Philippe (BMC Medical Education, 2013)
Background: Health science education faces numerous challenges: assimilation of knowledge, management of increasing numbers of learners or changes in educational models and methodologies. With the emergence of e-learning, the use of information and communication technologies (ICT) and Internet to improve teaching and learning in health science training institutions has become a crucial issue for low and middle income countries, including sub-Saharan Africa. In this perspective, the Faculty of Medicine and Biomedical Sciences (FMBS) of Yaoundé has played a pioneering role in Cameroon in making significant efforts to improve students’ and lecturers’ access to computers and to Internet on its campus. The objective is to investigate how computer literacy and the perception towards e-learning and its potential could contribute to the learning and teaching process within the FMBS academic community. Method: A cross-sectional survey was carried out among students, residents and lecturers. The data was gathered through a written questionnaire distributed at FMBS campus and analysed with routine statistical software. Results: 307 participants answered the questionnaire: 218 students, 57 residents and 32 lecturers. Results show that most students, residents and lecturers have access to computers and Internet, although students’ access is mainly at home for computers and at cyber cafés for Internet. Most of the participants have a fairly good mastery of ICT. However, some basic rules of good practices concerning the use of ICT in the health domain were still not well known. Google is the most frequently used engine to retrieve health literature for all participants; only 7% of students and 16% of residents have heard about Medical Subject Headings (MeSH). The potential of e-learning in the improvement of teaching and learning still remains insufficiently exploited. About two thirds of the students are not familiar with the concept of e-leaning. 84% of students and 58% of residents had never had access to e-learning resources. However, most of the participants perceive the potential of e-learning for learning and teaching, and are in favour of its development at the FMBS. Conclusion: The strong interest revealed by the study participants to adopt and follow-up the development of elearning, opens new perspectives to a faculty like the FMBS, located in a country with limited resources. However, the success of its development will depend on different factors: the definition of an e-learning strategy, the implementation of concrete measures and the adoption of a more active and participative pedagogy.
KerkoCite.ItemAlsoKnownAs: 10.1186/1472-6920-13-57 10/gb332f 2339240:UWNK53WJ 2405685:B67TQHQM

Staying or leaving? Designing for persistence in an online educator training programme in Indonesia - Burns, Mary (Open Learning: The Journal of Open, Distance and e-Learning, 2013)
This case study discusses factors impacting the attrition and persistence rates of 60 Indonesian educators in an online programme in 2010. Course designers developed three variations of a web-based programme – a fully online, hybrid and web-facilitated model – and placed 20 learners, all with similar technology skills, in the three different models. The online cohort experienced a 31% attrition rate while 100% of learners in the hybrid and web-facilitated models completed the programme. Data collection revealed that the greatest factor impacting attrition or persistence was the absence or presence of face-to-face interaction with the instructor and colleagues. This paper outlines programme design elements that learners found most helpful in successfully completing the course.
shortDOI: 10/ggx3rg KerkoCite.ItemAlsoKnownAs: 10.1080/02680513.2013.851023 10/ggx3rg 2339240:Z3PSB7EP 2339240:Z4Q6JPIM 2405685:FQJN7IPM 2405685:IPRAAK3V 2405685:M5M8WHW2 2405685:QM54QTRZ
Keywords: Indonesia; completion; online learning; persistence; readiness

Development and evaluation of Ning social network for teaching training online surveillance - Mohd Nawi, Mohd Aliff; Jamsari, Ezad Azraai; Sulaiman, Adibah; Hamzah, Mohd Isa (Turkish Online Journal of Distance Education, 2013)
Supervision of teaching practice is an important aspect of training teachers in improving their teaching skills. Barriers such as distance and time factor are the constraints faced by the lecturers at the National University of Malaysia to communicate with the teacher trainees under their supervision. Therefore, this study aims to develop and evaluate a social-networking site Ning's platform for the supervision of lecturers to teach on-line training. This study used the case design where a total of nine teacher trainees involved in this study. It found that overall, acceptance of the use of the social-networking site Ning mean score at the highest level of 3.91. In addition, all student teachers have positive attitudes towards the use of the social-networking site Ning social-networking site and agree a suitable approach to the supervision of one of the online teaching practices. While the "blog" is the most active facility used by student teachers in which they do self-reflection. In conclusion, the social-networking site Ning has the potential to assist lecturers to carry out supervision on-line teaching practice. (Contains 5 figures and 1 table.)
Publisher: Anadolu University, Office of the Rector, Eskisehir, 26470, Turkey KerkoCite.ItemAlsoKnownAs: 2405685:XGBJE4CK 2534378:5L9R6WLC 2534378:MFQCBZSB
Keywords: Courseware; ERIC; Current Index to Journals in Education (CIJE); Foreign Countries; Higher Education; Interviews; Malaysia; Observation; Online Courses; Social Networks; Student Teachers; Supervisory Methods; Teacher Education Programs; Teacher Supervision; Teaching Methods; Trainees; Web 2.0 Technologies; __:import:01; __:match:final; __:matched; __:study_id:2098097; __finaldtb; ⛔ No DOI found